Summary of the 2018 Alcohol and Immunology Research Interest Group (AIRIG) meeting - Kuprys, Paulius V. (Alcohol, 2018)
On January 26, 2018, the 23rd annual Alcohol and Immunology Research Interest Group (AIRIG) meeting was held at the University of Colorado Denver, Anschutz Medical Campus, Aurora, Colorado. The meeting consisted of plenary sessions with oral presentations and a poster presentation session. There were four plenary sessions that covered a wide range of topics relating to alcohol use: Alcohol and Liver Disease; Alcohol, Inflammation and Immune Response; Alcohol and Organ Injury; Heath Consequences and Alcohol Drinking. The meeting provided a forum for the presentation and discussion of novel research findings regarding alcohol use and immunology.